Immune aging: biological mechanisms, clinical symptoms, and management in lung transplant recipients - Kapse, Bhavya; Budev, Marie M.; Singer, Jonathan P.; Greenland, John R. (Frontiers in Transplantation, 2024)
While chronologic age can be precisely defined, clinical manifestations of advanced age occur in different ways and at different rates across individuals. The observed phenotype of advanced age likely reflects a superposition of several biological aging mechanisms which have gained increasing attention as the world contends with an aging population. Even within the immune system, there are multiple age-associated biological mechanisms at play, including telomere dysfunction, epigenetic dysregulation, immune senescence programs, and mitochondrial dysfunction. These biological mechanisms have associated clinical syndromes, such as telomere dysfunction leading to short telomere syndrome (STS), and optimal patient management may require recognition of biologically based aging syndromes. Within the clinical context of lung transplantation, select immune aging mechanisms are particularly pronounced. Indeed, STS is increasingly recognized as an indication for lung transplantation. At the same time, common aging phenotypes may be evoked by the stress of transplantation because lung allografts face a potent immune response, necessitating higher levels of immune suppression and associated toxicities, relative to other solid organs. Age-associated conditions exacerbated by lung transplant include bone marrow suppression, herpes viral infections, liver cirrhosis, hypogammaglobulinemia, frailty, and cancer risk. This review aims to dissect the molecular mechanisms of immune aging and describe their clinical manifestations in the context of lung transplantation. While these mechanisms are more likely to manifest in the context of lung transplantation, this mechanism-based approach to clinical syndromes of immune aging has broad relevance to geriatric medicine.